Bank capital forbearance and serial gambling - Natalya Martynova; Enrico C. Perotti; Javier Suárez (Deutsche Bundesbank, 2020)
We analyze the strategic interaction between undercapitalized banks and a supervisor who may intervene by preventive recapitalization. Supervisory forbearance emerges because political and fiscal costs undermine supervisors' commitment to intervene. When supervisors have lower credibility, banks' incentives to voluntary recapitalize are lower and supervisors may end up intervening more. Importantly, when intervention capacity is constrained (e.g. for fiscal reasons), private recapitalization decisions become strategic complements, producing equilibria with extremely high forbearance and high systemic costs. Anticipating forbearance in response to diffuse undercapitalization, banks may ex ante choose more correlated risks, a form of "serial gambling" undermining the supervisory response.
Keywords: G21; G28; 330; bank supervision; bank recapitalization; forbearance